The P2X7 receptor–NLRP3 inflammasome complex predicts the development of non‐Hodgkin's lymphoma in Sjogren's syndrome: a prospective, observational, single‐centre study. (6th June 2017) - Baldini, C.; Santini, E.; Rossi, C.; Donati, V.; Solini, A.
Abstract: Background: P2X7 receptor (P2X7R), trigger of acute inflammatory responses via the NLRP3 inflammasome, is hyperfunctioning in patients with Sjögren's syndrome (SS), where it stimulates IL‐18 production. Some patients with SS develop a mucosa‐associated lymphoid tissue non‐Hodgkin's lymphoma (MALT‐NHL). Objectives: To prospectively evaluate the involvement and the putative prognostic role of this inflammatory pathway in the development of MALT‐NHL. Methods: A total of 147 women with SS have been prospectively followed for a mean of 52 months, relating the expression and function of the P2X7R–inflammasome axis in salivary glands and circulating lymphomonocytes to the prognosis and the degree of the disease. Results: At baseline, gene expression of P2X7R and of the inflammasome components NLRP3, caspase‐1 and IL‐18 increased according to the presence of germinative centres and was higher in autoantibody‐positive individuals and strongly higher in those developing a MALT‐NHL over the follow‐up. Glandular expression of IL‐18 was threefold higher in MALT‐NHL than in controls or in the other patients with SS. P2X7R did not colocalize with generic markers of inflammatory infiltrate, like CD20, being selectively expressed by epithelial cells. P2X4R, sharing functional characteristics with P2X7R, did not differ in SS and controls. The increased P2X7R gene and protein expression was tissue specific, no difference being observed in peripheral lymphomonocytes between SS with MALT‐NHL and SS not developing MALT‐NHL. Conclusion: We propose the P2X7R–inflammasome axis as a novel potential pathway involved in both SS exocrinopathy and lymphomagenesis, reinforcing the hypothesis of a key role of IL‐18, via its increased P2X7R‐mediated production, in the pathogenesis of lymphoproliferative malignancies, and opening novel opportunities for the early diagnosis of lymphoproliferative complications and the development of potential targeted therapies.